PENGARUH EFIKASI DIRI, DISIPLIN KERJA DAN PELAYANAN TERHADAP KINERJA PEGAWAI PUSKESMAS DI KECAMATAN LEMPUING JAYA KABUPATEN OGAN KOMERING ILIR - Eko Susanto (Universitas Muhammadiyah Metro Lampung, 2018)
This research is based on the importance of improving the performance of health center staff who can give positive impact in achieving agency goals through performance measurement, puskesmas are encouraged to give good value to the organization activity and improve service for the society. When self efficacy and job discipline are low, the employee can not provide maximum service and indirectly it will affect the performance of health personnel. In this study using primary data collected by survey method and technique of sampling in the form of purposive sampling on 103 employees using questionnaires with Likert scale at Puskesmas in Lempuing Jaya Subdistrict Ogan Komering ilir Regency. Data quality testing uses validity and reliability test. Normality test, variance homogeneity test, linearity test and regression significance as test of requirements analysis and data analysis technique using path analysis.Based on the result of the research using path analysis showed that self efficacy (X1) had a positive direct effect on service (X3) of 0,018, work discipline (X2) did not positively influence the service (X3) 0,010, self efficacy (X1) employee performance (Y) of 0.747, work discipline (X2) has no direct positive effect on employee performance (Y) of 0.013 and service (X3) has a direct positive effect on employee performance (Y) of 0.252.Keywords: self efficacy, discipline, employer performance service